Digital Economy, Digital Currency and Leverage Effect in the Post-epidemic Era - Lyu, Wenbo; Liu, Yueting (Theoretical Key Issues and Practical Development Trends of China’s Digital Economy, 2024)
This paper highlights the inescapable trend of digital currency growth by examining past currency patterns and explores the ties between digital currency and the digital economy. This report predicts the future improvement trend of digital money using China as a case study. China created the digital currency in the middle of the rapid expansion of private cryptocurrencies with the intention of supporting the digital economy and pledging to bring the digital renminbi and the digital economy worldwide. In 2022, China entered a cycle of loose fiscal and monetary policy, while Europe and the US were still enduring stagnation. China views digital fiat money and digital economic development as a breakthrough to drive the transformation of the current economic system, new inventive growth, and the safety of the whole supply chain in the context of the scissors gap. It has become one of the forefront countries in the digital field, with numerous experiences that can be learned by countries around the world. A mature financial service system and financial market allows the free exchange and circulation of currency, and even a mature and stable currency derivative trading market enhances the resilience of the currency ecosystem. This paper also creates the concept and calculation formula of the e-CNY Index, sets the year 2022 as the first year of the e-CNY with the initial value of the index at 100; it also gives suggestions for creating and calculating the China-style Digital Economy Index. The importance of these indices as new tools for tracking and evaluating the digital macroeconomy in China is presented, providing a promising direction for future in-depth research on digital fiat currency. Finally, the article conducts empirical data analysis from the perspective of China's digital renminbi, proves the promotion effect of digital legal currency with facts, and gives corresponding suggestions to government departments.